THE EFFECTS OF ENTREPRENEURIAL PASSION AND FAMILY SUPPORT ON ENTREPRENEURIAL DECISION: A STUDY OF WOMEN ENTREPRENEURS - Indri Berlianita; Yuhendri Leo Vrista (Universitas Muhammadiyah Tangerang, 2026)
This study seeks to examine how female entrepreneurs in the handicraft subsector in Padang City make entrepreneurial decision based on entrepreneurial passion and family support. Earlier research has produced mixed evidence concerning the effect of family support on entrepreneurial decision, while evidence focusing on women entrepreneurs in the handicraft subsector remains limited. This study is distinct in that it simultaneously examines the influence of entrepreneurial passion and family support on the entrepreneurial decision of women entrepreneurs in Padang's handicraft industry. Quantitative research methods were employed using questionnaires distributed to female entrepreneurs in the handicraft subsector in Padang City. Multiple linear regression was used to examine the influence of entrepreneurial passion and family support on entrepreneurial decision. The findings show that entrepreneurial passion significantly influences entrepreneurial decision, whereas family support has no significant partial effect. However, both variables jointly produce a significant regression model in explaining entrepreneurial decision. The findings suggest that entrepreneurial decision is driven primarily by entrepreneurial passion. The results of this study might not apply to other industries or areas because it only looked at women business owners in Padang City's handicraft subsector. The results provide insights for academics and practical references for stakeholders in understanding the factors influencing women's entrepreneurial decision.